Release film and film laminate
Patent Information
- Application Number
- JP2021028787
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-25
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-02-25
AI Technical Summary
【0015】 本発明によれば、フッ素化シリコーンを用いなくても、あるいはその使用量を減らしても、優れた軽剥離性及び帯電防止性、とりわけ、シリコーン粘着剤に対する、優れた軽剥離性及び帯電防止性を有する、新規な離型フィルムが提供され、その工業的な利用価値は高い。
Smart Images

Figure 0007639397000001 
Figure 0007639397000002 
Figure 0007639397000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a release film and a film laminate. [Background technology]
[0002] Polyester films have excellent properties such as mechanical strength, dimensional stability, flatness, heat resistance, chemical resistance, and optical properties, and also have excellent cost performance, and therefore are used in a variety of applications.
[0003] In recent years, the number of automobiles equipped with liquid crystal panels has been increasing. In-vehicle applications such as these are often exposed to high and low temperatures for long periods of time, so the adhesive used to bond the panel components is also required to have high weather resistance and heat resistance. Silicone adhesives, which are primarily made of silicone, are attracting attention as an adhesive that meets this requirement.
[0004] Silicone adhesives have excellent heat resistance, chemical resistance and transparency, and are characterized by their ability to adhere to materials such as silicone rubber, fluororesin and metals, which are difficult to adhere to with general adhesives, as well as excellent re-adhesiveness. Silicone pressure sensitive adhesives are used in the form of tapes (films) with an adhesive layer. Before use, they are usually stored with one or both sides covered with a release film, and the release film is generally peeled off before use.
[0005] As the release film used for this type of application, a silicone release film which is obtained by coating a base film with a silicone release agent is widely used. However, when such a silicone release film is coated with a silicone adhesive, the adhesive and the release film tend to adhere strongly to each other and become difficult to peel off because the chemical structures of the release agent and the adhesive are similar. Therefore, in order to reduce the peeling force of the silicone adhesive (to make it easier to release), fluorine has been introduced into the silicone release agent. For example, Patent Document 1 proposes a fluorinated silicone material into which a fluorine substituent has been introduced in order to exhibit releasability against silicone pressure sensitive adhesives.
[0006] Furthermore, polyester films have a common problem with plastic films in that they tend to generate static electricity and become charged up. This can cause problems at processing sites due to the adhesion or entrapment of foreign matter caused by static electricity.
[0007] In particular, in the case of release films, peeling static electricity may occur when peeling off from an adherend such as an adhesive, which may cause serious problems such as not only problems due to adhesion or entrapment of foreign matter, but also damage to nearby electronic elements due to static electricity interference, resulting in product defects. Therefore, static electricity countermeasures based on equipment in the manufacturing process alone are not necessarily sufficient, and antistatic treatment of the release film itself is desired.
[0008] Therefore, for example, Patent Documents 2 and 3 propose a release film having excellent releasability and excellent antistatic properties, which has an antistatic layer and a release layer in this order on the surface of a base film. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2011-201035 A [Patent Document 2] JP 2010-6079 A [Patent Document 3] JP 2014-151573 A Summary of the Invention [Problem to be solved by the invention]
[0010] The fluorinated silicone material disclosed in Patent Document 1 is a substance that has high chemical stability and low toxicity. However, since fluorinated silicones are expensive, there is a demand to reduce the amount of fluorinated silicone used.
[0011] Furthermore, in the case of release films such as those disclosed in Patent Documents 2 and 3, the number of layers to be laminated increases, which not only complicates the manufacturing process but also tends to increase potential problems between layers, such as poor adhesion.
[0012] Therefore, an object of the present invention is to provide a release film having a release layer that does not use a fluorinated silicone agent or that can reduce the amount of fluorinated silicone agent used, and that combines excellent releasability and antistatic properties. [Means for solving the problem]
[0013] In view of the above circumstances, the present inventors have conducted intensive research and found that the above problems can be easily solved by using a release film provided with a release layer having a specific composition that does not use fluorinated silicone or allows the amount of fluorinated silicone to be reduced, and have completed the present invention. That is, the present invention has the following aspects.
[0014] [1] A release film having a release layer formed on at least one surface of a base film from a coating liquid containing the following compounds (A), (B), (C) and (D): (A) one or more selected from (a) a polymer in which a compound consisting of thiophene or a thiophene derivative is doped with another anionic compound, and (b) a self-doped polymer having an anionic group in a compound consisting of thiophene or a thiophene derivative. (B) Sugar alcohol (C) One or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins (D) One or more compounds selected from the group consisting of fluorine compounds and long-chain alkyl compounds other than the fluorine compounds. [2] The release film according to [1], wherein the compound (B) is a sugar alcohol having 4 to 12 carbon atoms. [3] The release film according to [1] or [2], wherein the compound (B) is sorbitol. [4] The release film according to any one of [1] to [3], wherein the compound (C) is a polyester resin. [5] The release film according to any one of [1] to [4], wherein the content of the compound (B) is 3 to 100 times that of the compound (A) in terms of mass ratio. [6] The release film according to any one of [1] to [5], wherein the base film is a polyester film. [7] A release film according to any one of [1] to [6], wherein the peel strength between the release layer and the silicone adhesive layer is 900 mN / 5 cm or less. [8] A film laminate in which the release film according to any one of [1] to [7] is attached to an optical member via a silicone adhesive layer. [9] The film laminate according to [8], wherein the optical component is a resin film or a glass substrate.
[10] The film laminate according to [9], wherein the resin film is selected from the group consisting of a polyester film, a polyimide film, and a cyclic polyolefin film.
[11] The film laminate according to [9] or
[10] , which is a laminate film having a functional layer provided on the surface of the resin film that contacts the silicone adhesive layer.
[12] The film laminate described in
[11] , wherein the functional layer is another release layer.
[13] The film laminate according to
[12] , wherein the other release layer contains a curable silicone resin.
[14] The film laminate according to any one of [8] to
[13] , having a total thickness of 200 μm or less.
[15] The release film according to any one of [1] to [7], which is for protecting a silicone adhesive layer.
[16] The film laminate according to any one of [8] to
[14] , which is for protecting a silicone adhesive layer.
[17] The release film according to
[15] , which is for in-vehicle use.
[18] The film laminate according to
[16] , which is for use in a vehicle.
Advantages of the Invention
[0015] According to the present invention, even without using fluorinated silicone or by reducing its usage amount, a novel release film is provided that has excellent light releasability and antistatic properties, particularly excellent light releasability and antistatic properties with respect to silicone adhesives, and its industrial utility value is high.
Modes for Carrying Out the Invention
[0016] Hereinafter, an example of an embodiment of the present invention will be described in detail. However, the present invention is not limited to the embodiment examples described below, and can be arbitrarily modified and implemented without departing from the gist of the present invention. In this specification, the term "A to B" regarding the description of numerical values means "A or more and B or less" (when A < B) or "A or less and B or more" (when A > B). In the present invention, a combination of preferred embodiments is a more preferred embodiment. In this specification, when the expression "(meth)acrylic acid" is used, it means one or both of "acrylic acid" and "methacrylic acid". Similarly, "(meth)acrylate" means one or both of "acrylate" and "methacrylate", and "(meth)acryloyl" means one or both of "acryloyl" and "methacryloyl".
[0017] <Release Film> Hereinafter, each member will be described in more detail. First, each member constituting the release film will be described in further detail. [Base Material Film] The base material film constituting the release film is not particularly limited as long as it is in the form of a film. For example, it may be made of paper, resin, metal, etc. Among these, from the viewpoints of mechanical strength and flexibility, it is preferably made of resin.
[0018] Examples of the resin substrate film include resin films formed from polymers such as polyethylene, polypropylene, cycloolefin polymer (COP), polyester, polystyrene, acrylic resin, polycarbonate, polyurethane, triacetyl cellulose (TAC), polyvinyl chloride, polyethersulfone, polyamide, polyimide, polyamideimide, etc. Furthermore, as long as it is possible to form a film, it may be a mixture of these materials (polymer blend) or a composite of the structural units (copolymer).
[0019] Among the above-listed substrate films, polyester films are particularly preferred because they have excellent physical properties such as heat resistance, flatness, optical properties, and strength. The polyester film may have a single layer structure or a multi-layer structure. When the polyester film has a multi-layer structure, the polyester film may have a two-layer structure, a three-layer structure, or a four-layer structure or more without departing from the gist of the present invention, and the number of layers is not particularly limited. The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a uniaxially or biaxially stretched film is preferable. Of these, a biaxially stretched film is more preferable from the viewpoints of balance of mechanical properties, flatness, and thinning.
[0020] The polyester used as the raw material for the polyester film may be either a homopolyester or a copolymer polyester. In the case of a homopolyester, it is preferable that the homopolyester is obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of aromatic dicarboxylic acids include terephthalic acid, 2,6-naphthalenedicarboxylic acid, etc. Examples of aliphatic glycols include ethylene glycol, diethylene glycol, 1,4-cyclohexanedimethanol, etc. A representative polyester is polyethylene terephthalate, etc. On the other hand, examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, and oxycarboxylic acid, and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 4-cyclohexanedimethanol, and neopentyl glycol.
[0021] The polyester polymerization catalyst is not particularly limited, and any conventionally known compound can be used, such as titanium compounds, germanium compounds, antimony compounds, manganese compounds, aluminum compounds, magnesium compounds, and calcium compounds.
[0022] In order to suppress the amount of precipitation of oligomer components, the film may be produced using a polyester having a low content of oligomer components as the raw material. As a method for producing a polyester having a low content of oligomer components, various known methods can be used, such as a method of performing solid phase polymerization after the production of a polyester. The amount of precipitation of oligomer components may be suppressed by forming the polyester film into a three-layer or more layer configuration and using a polyester raw material having a low content of oligomer components as the outermost layer of the polyester film. The polyester may also be obtained by carrying out the esterification or transesterification reaction, followed by melt polycondensation at a higher reaction temperature under reduced pressure.
[0023] It is also possible to incorporate an ultraviolet absorbing agent into the polyester film in order to improve the weather resistance of the film and prevent deterioration of the adherend (e.g., liquid crystal), etc. The ultraviolet absorbing agent is a compound that absorbs ultraviolet light and is not particularly limited as long as it can withstand the heat applied during the manufacturing process of the polyester film.
[0024] As the ultraviolet absorbing agent, there are organic ultraviolet absorbing agents and inorganic ultraviolet absorbing agents, and from the viewpoint of transparency, organic ultraviolet absorbing agents are preferred.As the organic ultraviolet absorbing agent, there are no particular limitations, but for example, cyclic imino esters, benzotriazoles, benzophenones, etc. are mentioned.From the viewpoint of durability, cyclic imino esters and benzotriazoles are more preferred.In addition, it is also possible to use two or more kinds of ultraviolet absorbing agents in combination.
[0025] Particles may be blended into the polyester film for the main purpose of imparting easy slippage and preventing scratches during each process. The type of particles to be blended is not particularly limited as long as it is a particle capable of imparting easy slippage, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenolic resin, epoxy resin, and benzoguanamine resin. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process may also be used.
[0026] The shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. may be used. There are also no particular limitations on the hardness, specific gravity, color, etc. Two or more types of these particles may be used in combination as necessary.
[0027] The average particle size of the particles used is usually 5 μm or less, preferably in the range of 0.01 to 3 μm. If it is 5 μm or less, the surface roughness of the film does not become too rough, which is preferable since it does not cause problems when various surface functional layers are formed in a later process.
[0028] Furthermore, the content of particles in the polyester film is usually less than 5% by mass, preferably in the range of 0.0003 to 3% by mass. When there are no particles or only a small amount of particles, the film has high transparency and is of good quality, but the slipperiness may be insufficient, so that it may be necessary to take measures such as adding particles to the coating layer to improve the slipperiness. Furthermore, if the particle content is less than 5% by mass, the transparency of the film can be sufficiently ensured. When particles are contained, for example, it is preferable to provide a surface layer and an intermediate layer and to contain particles in the surface layer. In this case, it is more preferable to form a multilayer structure having a surface layer containing particles, an intermediate layer, and a surface layer containing particles in this order.
[0029] The method of adding particles to the polyester film is not particularly limited, and any conventionally known method can be adopted. For example, in the case of a multi-layer polyester film, the particles can be added at any stage of the production of the polyester constituting each layer, but it is preferable to add the particles after the completion of the esterification or transesterification reaction.
[0030] In addition to the above-mentioned particles, conventionally known antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, etc. may be added to the polyester film as necessary.
[0031] The thickness of the polyester film is not particularly limited as long as it is within a range that allows formation of a film, but is preferably in the range of 5 to 350 μm, more preferably 8 to 125 μm, still more preferably 10 to 100 μm, and particularly preferably 12 to 75 μm.
[0032] Next, a specific example of the production of a polyester film will be described, but the production is not limited to the following production example. For example, when producing a biaxially stretched film, a method is preferred in which the dried pellets of the polyester raw material described above are extruded as a molten sheet from a die using an extruder, and then cooled and solidified with a cooling roll to obtain an unstretched sheet. In this case, it is preferred to increase the adhesion between the sheet and the rotating cooling drum in order to improve the flatness of the sheet, and an electrostatic application adhesion method and / or a liquid application adhesion method are preferably used. Next, the obtained unstretched sheet is stretched in biaxial directions. In this case, the unstretched sheet is first stretched in one direction by a roll or tenter type stretching machine. The stretching temperature is usually 70 to 120°C, preferably 80 to 110°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times. Next, the sheet is stretched in a direction perpendicular to the first-stage stretching direction, in which the stretching temperature is usually 70 to 170°C, and the stretching ratio is usually 3.0 to 7 times, preferably 3.5 to 6 times. Then, the film is subsequently heat-treated under tension or relaxation of 30% or less at a temperature of 180 to 270°C to obtain a biaxially stretched film. In the above stretching, a method of stretching in one direction in two or more stages can be adopted. In that case, it is preferable to perform the stretching so that the final stretch ratios in both directions are within the above ranges.
[0033] A simultaneous biaxial stretching method can also be used to produce the polyester film. The simultaneous biaxial stretching method involves simultaneously stretching and orienting the unstretched sheet in the machine direction and the width direction under a temperature controlled condition usually at 70 to 120° C., preferably 80 to 110° C., and the stretching ratio is preferably 4 to 50 times, more preferably 7 to 35 times, and even more preferably 10 to 25 times in terms of area ratio. Then, the film is subsequently heat-treated under tension or under relaxation of 30% or less at a temperature of 170 to 250° C. to obtain a stretched and oriented film. Regarding the simultaneous biaxial stretching device employing the above-mentioned stretching method, a conventionally known stretching method such as a screw method, a pantograph method, or a linear drive method can be employed.
[0034] [Release layer] The release film of the present invention is characterized in that it has a release layer formed on at least one surface of a base film from a coating liquid containing the following compounds (A), (B), (C) and (D). (A) one or more selected from (a) a polymer in which a compound consisting of thiophene or a thiophene derivative is doped with another anionic compound, and (b) a self-doped polymer having an anionic group in a compound consisting of thiophene or a thiophene derivative. (B) Sugar alcohol (C) One or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins (D) One or more compounds selected from the group consisting of fluorine compounds and long-chain alkyl compounds other than the fluorine compounds.
[0035] (Compound (A)) The compound (A) used in the present invention is at least one selected from (a) a polymer obtained by doping a compound made of thiophene or a thiophene derivative with another anionic compound, and (b) a self-doped polymer having an anionic group in a compound made of thiophene or a thiophene derivative. Examples of the compound (A) include those obtained by polymerizing a compound of the following formula (1) or (2) in the presence of a polyanion. The polymer (a) and the polymer (b) may be used in combination.
[0036] [ka] In the above formula (1), R 1 and R 2 each independently represents a hydrogen atom or an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, or the like having 1 to 20 carbon atoms.
[0037] [ka] In the above formula (2), n represents an integer of 1 to 4.
[0038] Examples of polyanions used in polymerization include poly(meth)acrylic acid, polymaleic acid, polystyrene sulfonic acid, polyvinyl sulfonic acid, etc. As a method for producing such a polymer, for example, a method such as that shown in JP-A-7-90060 can be adopted.
[0039] In the present invention, the compound of the above formula (2) in which n is 2 and polystyrene sulfonic acid is used as the polyanion is preferably used.
[0040] When these polyanions are acidic, they may be partially or completely neutralized. The base used for neutralization is preferably ammonia, organic amines, or alkali metal hydroxides.
[0041] The proportion of compound (A) in the total non-volatile components in the coating liquid is preferably 0.01 to 50 mass%, more preferably 0.5 to 20 mass%, and even more preferably 1 to 10 mass%. When the content of compound (A) is equal to or less than the upper limit, the strength and transparency of the release layer are good. On the other hand, when the content of compound (A) is equal to or more than the lower limit, sufficient antistatic properties are obtained.
[0042] (Compound (B)) The compound (B) used in the present invention is one or more sugar alcohols. By including a sugar alcohol in the release layer, the release properties are not hindered, and both high antistatic properties and high transparency can be achieved.
[0043] The sugar alcohol refers to a chain polyhydric alcohol obtained by reducing the carbonyl group of aldose or ketose, or a cyclic polyhydric alcohol such as cyclitol. Specific examples include chain sugar alcohols such as erythritol, threitol, and other C4 sugar alcohols obtained by reducing monosaccharides; ribitol, arabinitol, xylitol, and other C5 sugar alcohols; sorbitol, mannitol, iditol, talitol, galactitol, and other C6 sugar alcohols. In addition, cyclic sugar alcohols such as cyclitols such as inositol can be used. In addition, disaccharide alcohols such as maltitol, lactitol, and reduced isomaltulose obtained by reducing disaccharides can be used. In addition, when the sugar alcohol has stereoisomers, all of the stereoisomers are included. The sugar alcohol may be used alone or in combination of two or more kinds.
[0044] From the viewpoint of not inhibiting releasability and achieving both high antistatic properties and high transparency, the sugar alcohol is preferably a sugar alcohol having 4 to 12 carbon atoms, more preferably a sugar alcohol having 4 to 6 carbon atoms, and particularly preferably a sugar alcohol having 6 carbon atoms. Chain sugar alcohols are preferred. From the above viewpoint, it is preferred to use sorbitol among the sugar alcohols.
[0045] The proportion of compound (B) in the total non-volatile components in the coating solution is preferably 5 to 95% by mass, more preferably 10 to 90% by mass, and even more preferably 30 to 80% by mass. When the content of compound (B) is equal to or less than the upper limit, the coating film has sufficient water resistance. On the other hand, when the content of compound (B) is equal to or more than the lower limit, a uniform coating film having sufficient transparency and film-forming properties can be obtained.
[0046] From the viewpoints of transparency and antistatic properties, it is preferable to use compound (B) in a larger amount than compound (A). The content of compound (B) in the non-volatile components in the coating liquid is usually 3 to 100 times, preferably 5 to 50 times, and more preferably 7 to 25 times that of compound (A) in terms of mass ratio.
[0047] (Compound (C)) The compound (C) used in the present invention is one or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins. The release layer contains one or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins, and the film-forming properties, transparency, peelability, etc. of the release layer are improved.
[0048] ((Polyurethane resin)) The urethane resin is a polymeric compound having a urethane bond in the molecule, and is preferably water-dispersible or water-soluble. In the present invention, they may be used alone or in combination of two or more kinds.
[0049] In order to impart water dispersibility or water solubility, it is common and preferable to introduce hydrophilic groups such as hydroxyl groups, carboxyl groups, sulfonic acid groups, sulfonyl groups, phosphoric acid groups, ether groups, etc., into the urethane resin. Among the above hydrophilic groups, carboxyl groups and sulfonic acid groups are particularly preferable in terms of coating film properties and adhesion.
[0050] One of the methods for producing urethane resin is by the reaction of a hydroxyl group-containing compound with an isocyanate. As the hydroxyl group-containing compound used as a raw material, polyol is preferably used, for example, polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, and acrylic polyols. These compounds may be used alone or in combination.
[0051] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.
[0052] Examples of polyester polyols include polycarboxylic acids (malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, isophthalic acid, etc.) or their acid anhydrides and polyhydric alcohols (ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 2-methyl-1,3-propanediol, 1,6 ... 2-ethyl-2,4-pentanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamines, lactonediols, etc.
[0053] Examples of polycarbonate-based polyols include polycarbonate diols obtained by dealcoholization reaction of polyhydric alcohols with dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, etc., such as poly(1,6-hexylene) carbonate and poly(3-methyl-1,5-pentylene) carbonate.
[0054] Of these, polyester polyols are preferred.
[0055] Examples of polyisocyanate compounds used to obtain urethane resins include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and tolidine diisocyanate; aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethyl xylylene diisocyanate; aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidenedicyclohexyl diisocyanate. These may be used alone or in combination.
[0056] A chain extender may be used when synthesizing the urethane resin. The chain extender is not particularly limited as long as it has two or more active groups that react with an isocyanate group, and generally, a chain extender having two hydroxyl groups or two amino groups can be mainly used.
[0057] Examples of chain extenders having two hydroxyl groups include glycols such as aliphatic glycols such as ethylene glycol, propylene glycol, and butanediol; aromatic glycols such as xylylene glycol and bishydroxyethoxybenzene; and ester glycols such as neopentyl glycol hydroxypivalate.
[0058] Examples of chain extenders having two amino groups include aromatic diamines such as tolylenediamine, xylylenediamine, and diphenylmethanediamine; aliphatic diamines such as ethylenediamine, propylenediamine, hexanediamine, 2,2-dimethyl-1,3-propanediamine, 2-methyl-1,5-pentanediamine, trimethylhexanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine; and alicyclic diamines such as 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, dicyclohexylmethanediamine, 1,4-diaminocyclohexane, and 1,3-bisaminomethylcyclohexane.
[0059] ((Polyester resin)) The polyester resin may be composed of, as main components, for example, the following polyvalent carboxylic acids and polyvalent hydroxy compounds. That is, examples of polyvalent carboxylic acids that can be used include terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof. Examples of polyhydric hydroxy compounds include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, and potassium dimethylolpropionate. One or more of these compounds may be appropriately selected from each of them, and a polyester resin may be synthesized by a conventional polycondensation reaction.
[0060] In addition, a product obtained by copolymerizing sulfoisophthalic acid as a part of the polycarboxylic acid, introducing a sulfonic acid group into the polyester skeleton, and neutralizing it to make it hydrophilic is preferably used. The amount of copolymerization is usually 1 to 10 mol %, preferably 2 to 8 mol %, based on the total amount of polycarboxylic acid. By introducing an appropriate amount of sulfonic acid group, the water dispersion stability can be further improved.
[0061] ((Acrylic resin)) The acrylic resin is a polymer made of polymerizable monomers including acrylic and methacrylic monomers. These may be homopolymers or copolymers, or copolymers with polymerizable monomers other than acrylic and methacrylic monomers. Also included are copolymers of these polymers with other polymers (such as polyesters and polyurethanes). For example, block copolymers and graft copolymers. That is, the acrylic resin may be an acrylic-modified polyester resin or an acrylic-modified polyurethane resin. Alternatively, it also includes a polymer (or a mixture of polymers, as the case may be) obtained by polymerizing a polymerizable monomer having a carbon-carbon double bond in a polyester solution or polyester dispersion. Similarly, it also includes a polymer (or a mixture of polymers, as the case may be) obtained by polymerizing a polymerizable monomer having a carbon-carbon double bond in a polyurethane solution or polyurethane dispersion. Similarly, it also includes a polymer (or a mixture of polymers, as the case may be) obtained by polymerizing a polymerizable monomer having a carbon-carbon double bond in another polymer solution or dispersion. In order to further improve adhesion to the base film, a hydroxyl group or an amino group may be contained.
[0062] The polymerizable monomer having a carbon-carbon double bond is not particularly limited, but particularly representative compounds include, for example, various carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutyl hydroxyfumarate, and monobutyl hydroxyitaconate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, lauryl (meth)acrylate, and the like. Examples of such compounds include various alkyl (meth)acrylic acid esters such as acrylates; various nitrogen-containing compounds such as (meth)acrylamide, diacetone acrylamide, or (meth)acrylonitrile; nitrogen-containing compounds containing a hydroxyl group such as N-methylol (meth)acrylamide; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, and vinyl toluene; various vinyl esters such as vinyl propionate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane; phosphorus-containing vinyl monomers; various vinyl halides such as vinyl chloride and vinylidene chloride; and various conjugated dienes such as butadiene.
[0063] Among the above acrylic resins, polymers obtained by polymerizing polymerizable monomers including acrylic and methacrylic monomers are preferred, and it is more preferred that the polymerizable monomers include alkyl (meth)acrylic esters. In addition, in the case where the coating liquid is an aqueous system, from the viewpoint of facilitating dissolving or dispersing the compound (C), it is preferable that the polymerizable monomer has a hydrophilic group such as a hydroxyl group or a carboxyl group. Therefore, the acrylic resin is also preferably a polymer obtained by polymerizing a polymerizable monomer including an alkyl (meth)acrylic acid ester and a hydrophilic group-containing monomer such as a hydroxyl group-containing monomer or a carboxyl group-containing monomer. The acrylic resin may also be an emulsion polymer obtained by polymerizing a polymerizable monomer in the presence of a surfactant.
[0064] As the compound (C), a polyurethane resin or a polyester resin is preferable, and a polyester resin is more preferable, and from the viewpoint of coating film strength, a polyester having a naphthalene skeleton is further preferable.
[0065] The proportion of compound (C) in the total non-volatile components in the coating liquid is preferably in the range of 0.5 to 80 mass%, more preferably 1 to 50 mass%, and even more preferably 2 to 25 mass%. When the content of compound (C) is equal to or less than the upper limit, releasability and antistatic properties are sufficient. On the other hand, when the content of compound (C) is equal to or greater than the lower limit, the coating strength becomes sufficient.
[0066] (Compound (D)) The compound (D) used in the present invention is one or more compounds selected from the group consisting of fluorine compounds and long-chain alkyl compounds other than the fluorine compounds. In order to improve releasability, the release layer must contain one or more compounds selected from the group consisting of fluorine compounds and alkyl compounds.
[0067] ((Fluorine compounds)) The fluorine compound is a compound containing fluorine atoms in the compound. From the viewpoint of the coating appearance by in-line coating, organic fluorine compounds are preferably used, for example, perfluoroalkyl group-containing compounds, polymers of olefin compounds containing fluorine atoms, aromatic fluorine compounds such as fluorobenzene, etc. From the viewpoint of mold releasability, it is preferable to use a compound having a perfluoroalkyl group. Furthermore, the fluorine compound can also be a compound containing a long chain alkyl compound as described later.
[0068] Examples of compounds having a perfluoroalkyl group include perfluoroalkyl group-containing (meth)acrylates such as perfluoroalkyl (meth)acrylate, perfluoroalkyl methyl (meth)acrylate, 2-perfluoroalkyl ethyl (meth)acrylate, 3-perfluoroalkyl propyl (meth)acrylate, 3-perfluoroalkyl-1-methylpropyl (meth)acrylate, and 3-perfluoroalkyl-2-propenyl (meth)acrylate, and polymers thereof; perfluoroalkyl methyl vinyl ether, 2-perfluoroalkyl ethyl vinyl ether, 3-perfluoropropyl vinyl ether, 3-perfluoroalkyl-1-methylpropyl vinyl ether, and 3-perfluoroalkyl-2-propenyl vinyl ether, and polymers thereof. Considering heat resistance and contamination, a polymer is preferable. The polymer may be a single compound or a polymer of multiple compounds. From the viewpoint of releasability, the perfluoroalkyl group preferably has a carbon atom number of 3 to 11. Furthermore, it may be a polymer with a compound containing a long-chain alkyl compound as described below. From the viewpoint of adhesion to the substrate, a polymer with vinyl chloride is also preferably used.
[0069] ((Long-chain alkyl compounds)) The long-chain alkyl compound is a compound having a straight-chain or branched alkyl group having usually 6 or more carbon atoms, preferably 8 or more carbon atoms, and more preferably 12 or more carbon atoms. Examples of the alkyl group include a hexyl group, an octyl group, a decyl group, a lauryl group, an octadecyl group, a behenyl group, etc. Examples of the compound having an alkyl group include various long-chain alkyl group-containing polymer compounds, long-chain alkyl group-containing amine compounds, long-chain alkyl group-containing ether compounds, long-chain alkyl group-containing quaternary ammonium salts, etc. In consideration of heat resistance and staining resistance, polymer compounds are preferred. From the viewpoint of effectively imparting releasability, it is more preferable that the resin be a polymer compound having a long-chain alkyl group on the side chain.
[0070] The polymer compound having a long-chain alkyl group in the side chain can be obtained by reacting a polymer having a reactive group with a compound having an alkyl group capable of reacting with the reactive group. Examples of the reactive group include hydroxyl group, amino group, carboxyl group, acid anhydride, etc. Examples of compounds having these reactive groups include polyvinyl alcohol, polyethyleneimine, polyethyleneamine, reactive group-containing polyester resin, reactive group-containing poly(meth)acrylic resin, etc. Among these, polyvinyl alcohol is preferable in consideration of releasability and ease of handling.
[0071] Examples of compounds having an alkyl group capable of reacting with the reactive group include long-chain alkyl group-containing isocyanates such as hexyl isocyanate, octyl isocyanate, decyl isocyanate, lauryl isocyanate, octadecyl isocyanate, and behenyl isocyanate, long-chain alkyl group-containing acid chlorides such as hexanoyl chloride, octanoyl chloride, decanoyl chloride, lauroyl chloride, octadecanoyl chloride, and behenoyl chloride, long-chain alkyl group-containing amines, and long-chain alkyl group-containing alcohols. Among these, in consideration of releasability and ease of handling, long-chain alkyl group-containing isocyanates are preferred, and octadecyl isocyanate is particularly preferred.
[0072] Furthermore, polymeric compounds having a long-chain alkyl group in the side chain can also be obtained by polymerization of a long-chain alkyl (meth)acrylate or copolymerization of a long-chain alkyl (meth)acrylate with another vinyl group-containing monomer. Examples of long-chain alkyl (meth)acrylate include hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, octadecyl (meth)acrylate, and behenyl (meth)acrylate.
[0073] The proportion of compound (D) in the total non-volatile components in the coating solution is preferably 1 to 80 mass%, more preferably 2 to 70 mass%, and even more preferably 5 to 50 mass%. When the content of compound (D) is equal to or less than the upper limit, the coating strength is good. On the other hand, when the content of compound (D) is equal to or more than the lower limit, the releasability is good.
[0074] (Compound (E)) The release layer according to the present invention may contain a crosslinking agent (E) for the purpose of improving the durability of the release layer. As the crosslinking agent, various known crosslinking agents can be used, for example, melamine compounds, epoxy compounds, carbodiimide compounds, oxazoline compounds, isocyanate compounds, silane coupling compounds, etc. Among these, melamine compounds, epoxy compounds, isocyanate compounds, and carbodiimide compounds are preferred from the viewpoint of suppressing the decrease in antistatic properties after exposure to air, and melamine compounds and epoxy compounds are more preferred from the viewpoint of coating film strength.
[0075] ((Melamine Compounds)) The melamine compound is a compound having a melamine skeleton in the compound, and for example, an alkylolated melamine derivative, a compound partially or completely etherified by reacting an alkylolated melamine derivative with an alcohol, and a mixture thereof can be used. As the alcohol used for etherification, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, isobutanol, etc. can be suitably used. The melamine compound may be either a monomer or a dimer or higher polymer, or a mixture of these. Furthermore, melamine may be partially co-condensed with urea or the like, and a catalyst may be used to increase the reactivity of the melamine compound.
[0076] ((Epoxy Compounds)) The epoxy compound is a compound having an epoxy group in the molecule, and examples thereof include condensations of epichlorohydrin, ethylene glycol, polyethylene glycol, glycerin, polyglycerin, bisphenol A, etc. with a hydroxyl group or an amino group, polyepoxy compounds, diepoxy compounds, monoepoxy compounds, and glycidylamine compounds. Examples of the polyepoxy compound include sorbitol polyglycidyl ether, polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, and trimethylolpropane polyglycidyl ether. Examples of diepoxy compounds include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether. Examples of the monoepoxy compound include allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether, and examples of the glycidylamine compound include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylamino)cyclohexane, etc. From the viewpoint of improving adhesion, polyether-based epoxy compounds are preferred. In terms of the amount of epoxy groups, a polyepoxy compound having three or more functional groups is more preferable than a difunctional compound.
[0077] ((Carbodiimide compound)) A carbodiimide compound is a compound having a carbodiimide structure, and is a compound having one or more carbodiimide structures in the molecule. For better adhesion, etc., a polycarbodiimide compound having two or more carbodiimide structures in the molecule is more preferred.
[0078] Carbodiimide compounds can be synthesized by conventionally known techniques, and generally, condensation reaction of diisocyanate compounds is used. The diisocyanate compounds are not particularly limited, and both aromatic and aliphatic compounds can be used, and specific examples include tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate.
[0079] The content of carbodiimide groups contained in the carbodiimide compound, in terms of carbodiimide equivalent (weight [g] of the carbodiimide compound required to provide 1 mol of carbodiimide groups), is usually in the range of 100 to 1000, preferably 250 to 800, and more preferably 300 to 700. By using within the above range, the durability of the coating film is improved.
[0080] Furthermore, within the scope of the present invention, in order to improve the water solubility or water dispersibility of the polycarbodiimide compound, a surfactant may be added, or a hydrophilic monomer such as a polyalkylene oxide, a quaternary ammonium salt of a dialkylamino alcohol, or a hydroxyalkylsulfonate may be added.
[0081] ((Oxazoline Compounds)) The oxazoline compound is a compound having an oxazoline group in the molecule, and in particular, a polymer containing an oxazoline group is preferred, and can be prepared by polymerization of an addition polymerizable oxazoline group-containing monomer alone or with other monomers. Examples of the addition polymerizable oxazoline group-containing monomer include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline, and one or a mixture of two or more of these can be used. Among these, 2-isopropenyl-2-oxazoline is suitable because it is easily available industrially. The other monomer is not limited as long as it is a monomer that can be copolymerized with the addition-polymerizable oxazoline group-containing monomer, and examples thereof include (meth)acrylic acid esters such as alkyl (meth)acrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrenesulfonic acid, and salts thereof (sodium salts, potassium salts, ammonium salts, tertiary amine salts, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylamide, N-alkyl (meth)acrylate, etc. Examples of the monomer include unsaturated amides such as t)acrylamide and N,N-dialkyl(meth)acrylamide (the alkyl group can be a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, a 2-ethylhexyl group, a cyclohexyl group, and the like); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride and vinylidene chloride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. One or more of these monomers can be used. The oxazoline compound may have a polyalkylene oxide chain such as a polyethylene oxide chain, and for example, a (meth)acrylate having a polyalkylene oxide chain may be used as another monomer. From the viewpoint of improving adhesion, the amount of oxazoline groups in the oxazoline compound is preferably in the range of 0.5 to 10 mmol / g, more preferably 1 to 9 mmol / g, further preferably 3 to 8 mmol / g, and particularly preferably 4 to 6 mmol / g.
[0082] ((Isocyanate Compounds)) The isocyanate compound is a compound having an isocyanate or an isocyanate derivative structure, such as a blocked isocyanate. Examples of the isocyanate include aromatic isocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic isocyanates having an aromatic ring, such as α,α,α',α'-tetramethyl xylylene diisocyanate; aliphatic isocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic isocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isopropylidenedicyclohexyl diisocyanate. In addition, polymers and derivatives such as biuretized products, isocyanurate products, uretdione products, and carbodiimide modified products of these isocyanates are also included. These may be used alone or in combination. Among the above isocyanates, aliphatic isocyanates or alicyclic isocyanates are more preferable than aromatic isocyanates in order to prevent yellowing due to ultraviolet rays.
[0083] When used in the form of a blocked isocyanate, examples of the blocking agent include bisulfites; phenolic compounds such as phenol, cresol, and ethylphenol; alcohol compounds such as propylene glycol monomethyl ether, ethylene glycol, benzyl alcohol, methanol, and ethanol; active methylene compounds such as isobutanoylmethyl acetate, dimethyl malonate, diethyl malonate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone; mercaptan compounds such as butyl mercaptan and dodecyl mercaptan; lactam compounds such as ε-caprolactam and δ-valerolactam; amine compounds such as diphenylaniline, aniline, and ethyleneimine; acid amide compounds such as acetanilide and acetic acid amide; and oxime compounds such as formaldehyde oxime, acetaldoxime, acetone oxime, methyl ethyl ketone oxime, and cyclohexanone oxime, which may be used alone or in combination of two or more.
[0084] The isocyanate compound may be used alone or as a mixture or bond with various polymers. In terms of improving the dispersibility and crosslinking property of the isocyanate compound, it is preferable to use a mixture or bond with a polyester resin or a urethane resin.
[0085] ((Silane coupling compound)) A silane coupling compound is an organosilicon compound that has an organic functional group and a hydrolyzable group such as an alkoxy group in one molecule. For example, epoxy group-containing compounds such as 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; vinyl group-containing compounds such as vinyltrimethoxysilane and vinyltriethoxysilane; styryl group-containing compounds such as p-styryltrimethoxysilane and p-styryltriethoxysilane; (meth)acrylic group-containing compounds such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)- Amino group-containing compounds such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and N-phenyl-3-aminopropyltriethoxysilane; isocyanurate group-containing compounds such as tris(trimethoxysilylpropyl)isocyanurate and tris(triethoxysilylpropyl)isocyanurate; mercapto group-containing compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropylmethyldiethoxysilane.
[0086] The proportion of compound (E) in the total non-volatile components in the coating liquid is preferably in the range of 0 to 60 mass%, more preferably 0 to 40 mass%, and even more preferably 0 to 25 mass%. By having compound (E) in the above range, the coating film durability of the release layer is improved.
[0087] (Compound (F)) In order to improve the coating property to the base film, the coating liquid used in the present invention preferably contains a surfactant as compound (F). As the surfactant, from the viewpoint of not inhibiting the antistatic property of the resulting release layer, a nonionic surfactant having one selected from polyalkylene oxide, polyglycerin, and derivatives thereof in its structure is more preferable, a nonionic surfactant having polyalkylene oxide is further preferable, and a nonionic surfactant having polyethylene oxide is particularly preferable.
[0088] Further, as the compound (F), a surfactant having a branched alkyl group-substituted acetylene structure or a fluoroalkyl group in the hydrophobic portion is more preferable. Examples of the surfactant having a branched alkyl group-substituted acetylene structure in the hydrophobic portion include nonionic surfactants having a structure having polyethylene oxide in the side chain, as shown in the following formula (3).
[0089] [ka] In the above formula (3), m and n are positive numbers indicating the number of moles of ethylene oxide added.
[0090] In the above formula (3), the average of m+n is preferably 1.3 or more and 30 or less, more preferably 2 or more and 20 or less, and further preferably 4 or more and 10 or less.
[0091] The surfactant of the compound (F) may be used alone or in combination of two or more kinds.
[0092] (Other ingredients) As long as the gist of the present invention is not impaired, particles can be used in combination for the purpose of improving blocking properties, slip properties, etc. Furthermore, in addition to the above components, additives such as reaction regulators and adhesion enhancers may be appropriately blended.
[0093] (solvent) The compounds (A) to (D) and the compounds (E), (F) and other components that are added optionally are diluted with a solvent to prepare a coating liquid. The liquid coating liquid is applied to a substrate film, and is dried and cured as necessary. The compounds (A) to (D) and the compounds (E), (F) and other components that are added optionally to the release layer may be dissolved in a solvent, or may be dispersed in the solvent. The solvent is not particularly limited, and either water or an organic solvent may be used, but from the viewpoint of environmental protection, it is preferable to use an aqueous coating liquid containing water as the main solvent (50% by mass or more). The water content is preferably 60% by mass or more, more preferably 70% by mass or more. The aqueous coating liquid may contain a small amount of an organic solvent. The specific amount of the organic solvent is preferably less than that of water on a mass basis, and is, for example, less than 30% by mass, preferably less than 20% by mass, more preferably less than 10% by mass in the solvent. Examples of organic solvents used in combination with water include alcohols such as ethanol, isopropanol, ethylene glycol, and glycerin, ethers such as ethyl cellosolve, t-butyl cellosolve, propylene glycol monomethyl ether, and tetrahydrofuran, ketones such as acetone and methyl ethyl ketone, esters such as ethyl acetate, and amines such as dimethylethanolamine. These can be used alone or in combination. By appropriately selecting and adding these organic solvents to the aqueous coating liquid as necessary, the stability and coatability of the coating liquid may be improved.
[0094] In addition, when an organic solvent is used alone as the above-mentioned solvent, examples of the organic solvent include aromatic hydrocarbons such as toluene, aliphatic hydrocarbons such as hexane, heptane, isooctane, esters such as ethyl acetate, butyl acetate, ketones such as ethyl methyl ketone (MEK), isobutyl methyl ketone, alcohols such as ethanol, 2-propanol, ethers such as diisopropyl ether, dibutyl ether, etc. These may be used alone or in combination, taking into consideration solubility, coatability, boiling point, etc.
[0095] It can be assumed that the release layer contains unreacted compounds such as the above compounds (A) to (D), reacted compounds, or a mixture thereof.
[0096] From the viewpoint of handleability, the total thickness of the release film of the present invention is preferably 200 μm or less, more preferably 5 μm or more and 125 μm or less, even more preferably 8 μm or more and 100 μm or less, and particularly preferably 12 μm or more and 75 μm or less.
[0097] (Method of producing release film (method of forming release layer)) The method for forming a release layer according to the present invention will be described below. The method for forming the release layer is not particularly limited, and any conventionally known coating method such as reverse gravure coating, direct gravure coating, roll coating, die coating, bar coating, curtain coating, etc. can be used. The method for forming the release layer includes in-line coating and off-line coating. The drying and curing conditions are not particularly limited, and for example, when the release layer is provided by off-line coating, it is usually recommended to perform heat treatment at 80 to 200°C for 3 to 40 seconds, preferably at 140 to 180°C for 3 to 40 seconds. On the other hand, when the release layer is provided by in-line coating, it is usually recommended to perform heat treatment at 70 to 280°C for 3 to 200 seconds.
[0098] In the present invention, the release layer is preferably formed by in-line coating, which treats the surface of the polyester film during the film-forming process. In-line coating is a method of coating within the polyester film production process, specifically, coating at any stage from melt extrusion of polyester to stretching, heat setting and winding up. Usually, coating is performed on any of the following: an unstretched sheet obtained by melting and quenching, a stretched uniaxially stretched film, a biaxially stretched film before heat setting, or a film after heat setting and before winding up. Although not limited to the following, for example, in the case of sequential biaxial stretching, a method in which a uniaxially stretched film stretched in the longitudinal direction (machine direction) is coated and then stretched in the transverse direction is particularly advantageous. This method has the advantage of being able to simultaneously form the film and the release layer, and is advantageous in terms of production costs. In addition, since stretching is performed after coating, the thickness of the release layer can be changed by the stretching ratio, and thin film coating can be performed more easily than with off-line coating films. Furthermore, by providing a release layer on the film before stretching, the release layer can be stretched together with the polyester film, thereby allowing the release layer to adhere firmly to the polyester film. Furthermore, in the production of biaxially stretched polyester film, the film can be restrained in the vertical and horizontal directions by stretching while holding the film ends with clips or the like, and high temperatures can be applied in the heat fixing process while maintaining flatness without wrinkles or the like. Therefore, the heat treatment performed after coating can be performed at a high temperature that cannot be achieved by other methods, improving the film-forming properties of the release layer and allowing the release layer and the polyester film to adhere more firmly. Furthermore, a strong release layer can be formed, and the adhesion to various functional layers that can be formed on the release layer, as well as the performance of moisture and heat resistance, can be improved.
[0099] Regardless of whether off-line coating or in-line coating is used, heat treatment and irradiation with active energy rays such as ultraviolet rays may be used in combination as necessary. The polyester film constituting the laminated polyester film of the present invention may be previously subjected to a surface treatment such as a corona treatment or a plasma treatment.
[0100] The coating amount of the non-volatile component of the release layer is preferably 1 to 300 mg / m 2 , more preferably 5 to 150 mg / m 2 , and more preferably 10 to 75 mg / m 2 , and particularly preferably 20 to 50 mg / m 2 If the coating amount of the release layer is within the above range, appropriate releasability from the silicone adhesive layer can be ensured.
[0101] <Release film properties> The haze of the release film of the present invention is preferably 10% or less, more preferably 5% or less, even more preferably 2.0% or less, and particularly preferably 1.0% or less. By being in the above range, inspection with the release film of the present invention attached can be easily performed in the manufacturing and processing steps using the release film of the present invention.
[0102] The peel strength between the release layer and the silicone adhesive layer of the release film of the present invention can be evaluated by the measurement method described in the Examples below. If the peel strength evaluated in this manner is 900 mN / 5 cm or less, it can be said to have good peelability, but it is preferably 500 mN / 5 cm or less, and more preferably 300 mN / 5 cm or less. There is no particular restriction on the lower limit, but from the viewpoint of avoiding unintended peeling when attached to an adhesive layer, for example, the lower limit is preferably 10 mN / 5 cm or more, and more preferably 15 mN / 5 cm or more.
[0103] The antistatic property of the release film of the present invention can be evaluated by measuring the surface resistivity of the surface of the release layer provided on the surface of the base film. The lower the surface resistivity of the release film surface (the surface of the release layer), the better the antistatic property. Surface resistivity is 1×10 12 If the resistance is less than 1×10 Ω / □, it can be said to have antistatic properties. 10 If it is less than Ω / □, it can be said that the antistatic property is good, and if it is less than 1×10 8 If the resistance is less than 1×10 Ω / □, it is considered to have excellent antistatic properties and is therefore preferable. 6 If it is Ω / □ or less, it can be said that the antistatic performance is particularly good. In addition, there is no particular lower limit for the surface resistivity, but considering the cost of this film, it is 1×10 4 It is preferable that the resistance is Ω / □ or more.
[0104] The above-mentioned compounds and components in the release layer can be analyzed by, for example, TOF-SIMS, ESCA, fluorescent X-ray analysis, or the like.
[0105] <Film laminate> The film laminate of the present invention has a configuration in which the release film is bonded to an optical member via a silicone adhesive layer.
[0106] [Silicone adhesive layer] The silicone adhesive layer is a layer composed of an adhesive containing silicone as a main component resin (hereinafter, also referred to as "silicone adhesive"). The "main component resin" refers to the resin that has the largest content (mass) among the resins that compose the adhesive. Examples of the silicone adhesive include addition reaction type, peroxide curing type, and condensation reaction type silicone adhesives. Among them, addition reaction type silicone adhesives are preferably used from the viewpoint of being curable at low temperature in a short time. Note that these addition reaction type silicone adhesives are cured when the adhesive layer is formed on the support. When an addition reaction type silicone pressure-sensitive adhesive is used as the silicone pressure-sensitive adhesive, the silicone pressure-sensitive adhesive may contain a catalyst such as a platinum catalyst. For example, the addition reaction type silicone adhesive can be prepared by, if necessary, diluting a silicone resin solution with a solvent such as toluene, adding a catalyst such as a platinum catalyst, stirring until homogeneous, applying the solution onto a support, and curing the solution at 100 to 130°C for 1 to 10 minutes. If necessary, a crosslinking agent or an additive for controlling adhesive strength may be added to the addition reaction type silicone adhesive, or the support may be subjected to a primer treatment before the adhesive layer is formed.
[0107] Commercially available silicone resins for use in the addition reaction type silicone pressure sensitive adhesive include SD4580PSA, SD4584PSA, SD4585PSA, SD4587LPSA, SD4560PSA, SD4570PSA, SD4600FCPSA, SD4593PSA, DC7651ADHESIVE, DC7652ADHESIVE, LTC-755, LTC-310 (all manufactured by Dow Corning Toray Co., Ltd.), KR-3700, KR-3701, KR-3704, X-40-3237-1, X-40-3240, X- Examples of such compounds include X-40-3291-1, X-40-3229, X-40-3323, X-40-3306, and X-40-3270-1 (all manufactured by Shin-Etsu Chemical Co., Ltd.), AS-PSA001, AS-PSA002, AS-PSA003, AS-PSA004, AS-PSA005, AS-PSA012, AS-PSA014, and PSA-7465 (all manufactured by Arakawa Chemical Industries Co., Ltd.), TSR1512, TSR1516, and TSR1521 (all manufactured by Momentive Performance Materials, Inc.). However, the examples are not limited to these.
[0108] [Optical components] The optical member is a resin film or a glass substrate. The resin film is preferably a resin film selected from the group consisting of a polyester film, a polyimide film, and a cyclic polyolefin film. In addition, it is preferable that the resin film is a laminated film in which a functional layer is provided on the surface of the resin film that contacts the silicone adhesive layer. The functional layer is preferably a release layer, which is a layer different from the release layer in the release film of the present invention, and is hereinafter referred to as "another release layer" for convenience.
[0109] The "other release layer" preferably contains a curable silicone resin from the viewpoint of releasability with respect to the silicone adhesive layer. An example of the "other release layer" is one having, in sequence, a first layer formed from a silicone composition containing as its main component a curable silicone resin that does not contain a fluorine substituent, and a second layer containing a component having a fluorine substituent.
[0110] Another example of the "other release layer" is a layer formed from a silicone composition containing, as a main component, a curable silicone resin containing a fluorine substituent.
[0111] Furthermore, another example of the "other release layer" is a layer formed from a silicone composition containing, as a main component, a curable silicone resin that does not contain a fluorine substituent.
[0112] The term "main component" used herein refers to the component that has the largest mass ratio among the constituent components.
[0113] From the viewpoint of handleability, the total thickness of the film laminate of the present invention is preferably 200 μm or less, more preferably 9 μm or more and 125 μm or less, even more preferably 12 μm or more and 125 μm or less, and particularly preferably 25 μm or more and 125 μm or less.
[0114] <Applications of release films and film laminates> From the viewpoint of having excellent releasability from silicone pressure-sensitive adhesives, the release film of the present invention can be suitably used as a light release film for silicone pressure-sensitive adhesives in the following forms, although the present invention is not limited to such uses. In a film laminate having a configuration in which the release film of the present invention (hereinafter referred to as "light release film") is laminated on one side of a silicone adhesive layer made of a silicone adhesive, and a release film (hereinafter referred to as "heavy release film") having a higher peel strength than this release film is laminated on the opposite side of the silicone adhesive layer, the light release film can be peeled off, the exposed surface of the silicone adhesive layer is attached to an "adherend", the silicone adhesive layer is cured, and then the heavy release film is peeled off. However, the use is not limited to this method.
[0115] The adherend may be an optical member, such as a resin film selected from a polyester film, a polyimide film, or a cyclic polyolefin film, or a glass substrate, as described above. In the film laminate of the present invention, a silicone pressure-sensitive adhesive having good durability and transparency can be used. Therefore, by taking advantage of the heat resistance, cold resistance, weather resistance and high transparency that the silicone adhesive itself possesses, it can be suitably used in displays such as touch panels, and can be particularly suitably used in vehicle-mounted displays such as car navigation systems.
[0116] <Method of manufacturing film laminate> The method for producing the film laminate of the present invention is not particularly limited, but for example, the film laminate of the present invention can be produced by applying a silicone adhesive layer-forming liquid onto the release layer of the release film of the present invention with an applicator to form a silicone adhesive layer, and then laminating another resin film or a glass substrate onto the silicone adhesive layer. The method for applying the silicone adhesive layer-forming liquid is not particularly limited, and can be carried out by a conventionally known method. As described above, the other resin film may have a functional layer on the surface that comes into contact with the silicone adhesive layer. EXAMPLES
[0117] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples without departing from the gist of the present invention. The measurement and evaluation methods used in the present invention are as follows.
[0118] <Evaluation method> (1) Intrinsic viscosity of polyester 1 g of polyester from which components incompatible with the polyester had been removed was precisely weighed out, dissolved in 100 mL of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and the viscosity was measured at 30°C using a viscosity (IV) measuring device (Rigo Co., Ltd., "VMS-022UPC·F10").
[0119] (2) Average particle size The films of the examples and comparative examples were observed using a transmission electron microscope (TEM) (Hitachi High-Tech Corporation, "H-7650", acceleration voltage 100 kV), and the average particle size of 10 particles was taken as the average particle size.
[0120] (3) Non-volatile content of coating fluid The measurements were performed using a halogen moisture meter (Mettler Toledo HR73) at 105°C for 60 minutes.
[0121] (4) Coating amount of release layer It was calculated from the non-volatile concentration of the coating liquid, the coating amount before drying derived from the consumption amount of the coating liquid, the transverse stretching ratio, etc.
[0122] (5) Film Haze Measurements were made in accordance with JIS K 7136 using a haze meter (manufactured by Murakami Color Research Laboratory, "HM-150").
[0123] (6) Peel strength of release layer The following silicone adhesive composition was applied to the surface of a film (same film as Comparative Example 4 described later) without a release layer, and heat-treated at 120°C for 6 minutes to form a silicone adhesive layer with a thickness of 5 μm. After aging at room temperature for 24 hours, the adhesive layer side of the film was attached to the release layer surface of the release film of the examples and comparative examples, pressed with a rubber roller, and cut into a width of 5 cm. This was left at room temperature for 24 hours to obtain an evaluation sample. The peeling force when peeling the release film from the silicone adhesive layer of the evaluation sample was measured, and this was taken as the peeling force of the release layer. The peel strength was measured using a tensile tester (manufactured by Shimadzu Corporation, "AGX-plus") at a tensile speed of 300 mm / min and 180° peeling. (Silicone pressure-sensitive adhesive composition) Silicone adhesive (KR-3700, manufactured by Shin-Etsu Chemical Co., Ltd.) 25 parts by weight Silicone adhesive (KR-3704, manufactured by Shin-Etsu Chemical Co., Ltd.) 25 parts by weight Curing catalyst (PL-50T, manufactured by Shin-Etsu Chemical Co., Ltd.) 0.25 parts by mass Toluene 50 parts by mass
[0124] (7) Surface resistivity of release layer The surface resistivity of the release layer surface was measured according to the following method (7-1). 8 Since it is not possible to measure a surface resistivity higher than Ω, the method of (7-2) was used for samples that could not be measured by (7-1). (7-1): A four-point ASP probe was used with a low resistivity meter (Mitsubishi Chemical Analytech Co., Ltd., "Loresta GP MCP-T600") to measure the surface resistivity near the center after conditioning the sample for 30 minutes in a measurement atmosphere of 23°C and 50% RH. The RCF value was kept constant at 4.235. (7-2): A high resistivity meter (Mitsubishi Chemical Analytech Co., Ltd., "Hiresta UX MCP-HT800") was used with UR-100 as the measurement electrode, and the surface resistivity was measured after conditioning the sample for 30 minutes in a measurement atmosphere of 23°C and 50% RH.
[0125] The polyester raw materials for the base films used in the examples and comparative examples are as follows:
[0126] <Polyester (1)> Substantially particle-free polyethylene terephthalate with an intrinsic viscosity of 0.64 dL / g
[0127] <Polyester (2)> Polyethylene terephthalate with an intrinsic viscosity of 0.65 dL / g containing 0.2% by mass of amorphous silica with an average particle size of 2.4 μm
[0128] The following materials were used for the coating solution for forming the release layer. (Compound (A)) (A1): Conductive agent "AS-G1" (manufactured by Shin-Etsu Polymer Co., Ltd., mainly composed of polyethylenedioxythiophene and polystyrenesulfonic acid) was neutralized with concentrated ammonia water to a pH of 9.
[0129] (Compound (B)) (B1): Sorbitol
[0130] (Compound (C)) (C1): Aqueous dispersion of polyester resin copolymerized with the following composition Monomer composition: (Acid component) 2,6-naphthalenedicarboxylic acid / 5-sodium sulfoisophthalic acid = 92 / 8 (molar ratio) (Diol component) Ethylene glycol / diethylene glycol = 80 / 20 (molar ratio)
[0131] (Compound (D)) (D1): A water dispersion of a long-chain alkyl compound obtained by reacting polyvinyl alcohol having an average degree of polymerization of 500 and a degree of saponification of 88 mol% with an excess of octadecyl isocyanate, purifying the reacted product, and dispersing the product in water using a nonionic dispersant. (D2): "Asahiguard E400" (manufactured by AGC Corporation, an aqueous dispersion of a copolymer compound whose main components are perfluoroalkyl group-containing acrylate and long-chain alkyl group-containing acrylate) (D3): "Unidyne TG5673" (manufactured by Daikin Industries, Ltd.; aqueous dispersion of copolymer compound mainly composed of perfluoroalkyl group-containing acrylate and long-chain alkyl group-containing acrylate) (D4): "Frelease 6012" (manufactured by NEOS Co., Ltd., an aqueous dispersion of a copolymer compound mainly composed of a branched perfluoroalkyl group-containing acrylate and a long-chain alkyl group-containing acrylate).
[0132] (Compound (E)) (E1): Polymethylol melamine (E2): Polyglycerol polyglycidyl ether
[0133] (Compound (F)) (F1): A nonionic surfactant having a structure having polyethylene oxide in the side chain, in which the average of m+n in the above formula (3) is 10. (F2): A fluorine-based nonionic surfactant having a structure in which the hydrophobic group has a branched perfluoroalkenyl group and the hydrophilic group has a polyethylene oxide chain (average chain length 8 units).
[0134] (Comparative compound (G)) (G1): Polyvinyl alcohol "GOHSENOL GL-05" (manufactured by Mitsubishi Chemical Corporation, saponification degree 88 mol%) (G2): Polyethylene glycol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., average molecular weight 1000)
[0135] Example 1 A blend of polyester (1) and polyester (2) in a mass ratio of 92 / 8 was used as the raw material for layer A, and polyester (1) alone was used as the raw material for layer B, which was fed into an extruder, heated and melted at 285°C, and co-extruded to a thickness ratio of A / B / A=5 / 90 / 5 under extrusion conditions, with layer A being the outermost layer (surface layer) and layer B being the middle layer, and then cooled and solidified while being in close contact with a mirror-finished cooling drum with a surface temperature of 40-50°C to produce an unstretched film. This film was stretched 3.7 times in the longitudinal direction while passing through a group of heated rolls at 85°C to produce a uniaxially stretched film. Coating solution 1 having the composition shown in Table 1 below was applied to one side of this uniaxially stretched film, and then the film was introduced into a tenter stretching machine and stretched 4.3 times in the width direction at 100°C. It was then heat-treated at 230°C and then relaxed by 2% in the width direction. After drying, the coating amount was 37 mg / m 2 Thus, a biaxially stretched film having a thickness of 50 μm and a release layer of this composition was obtained, obtaining the release film of Example 1. The evaluation results of this release film are shown in Table 2 below.
[0136] (Examples 2 to 5) The release films of Examples 2 to 5 were obtained in the same manner as in Example 1, except that the coating liquid for forming the release layer was changed to the coating liquid having the composition shown in Table 1 and the coating amount of the coating liquid was changed to the amount shown in Table 2. The evaluation results are shown in Table 2.
[0137] (Comparative Examples 1 to 3) The release films of Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the coating liquid for forming the release layer was changed to the coating liquid having the composition shown in Table 1 and the coating amount of the coating liquid was changed to the amount shown in Table 2. The evaluation results are shown in Table 2. In addition, in Comparative Examples 2 and 3, the antistatic property could not be confirmed in the above-mentioned measurement of the surface resistance value of the release layer, so the above-mentioned measurement of the peeling force of the release layer was not carried out.
[0138] Comparative Example 4 Except for not providing a release layer, a release film of Comparative Example 4 was obtained in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0139] [Table 1]
[0140] [Table 2]
[0141] The release films obtained in Examples 1 to 5 of the present invention had low haze and low surface resistance, and had excellent releasability and antistatic properties. Compared with Examples 1 to 5, Comparative Example 1 lacking compound (D) had a large peeling force, and sufficient releasability could not be obtained. Furthermore, compared with Examples 1 to 5, Comparative Examples 2 and 3, in which compound (B) was replaced with polyvinyl alcohol or polyethylene oxide, which are commonly used as water-soluble resins, had a high surface resistivity and were unable to obtain sufficient antistatic properties. The release film obtained by the present invention has excellent transparency even when the coating film is stretched, exhibits high antistatic properties even with an extremely small amount of conductive agent (compound (A)), and also has releasability to silicone pressure-sensitive adhesives, and is therefore excellent in productivity and economy.
Claims
1. A release film having a release layer formed on at least one surface of a base film from a coating liquid containing the following compounds (A), (B), (C) and (D), wherein the compound (A) accounts for 1 to 10 mass %, the compound (B) accounts for 30 to 80 mass %, the compound (C) accounts for 0.5 to 25 mass %, and the compound (D) accounts for 5 to 50 mass %, as a proportion of a total non-volatile component in the coating liquid; The content of the compound (B) is 5 to 50 times that of the compound (A) in terms of mass ratio. (A) at least one selected from (a) a polymer obtained by doping a compound consisting of thiophene or a thiophene derivative with another anionic compound, and (b) a self-doped polymer having an anionic group in a compound consisting of thiophene or a thiophene derivative. (B) Sugar alcohol (C) One or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins (D) One or more compounds selected from the group consisting of fluorine compounds and long-chain alkyl compounds other than the fluorine compounds.
2. The release film according to claim 1, wherein the compound (B) is a sugar alcohol having 4 to 12 carbon atoms.
3. The release film according to claim 1 or 2, wherein the compound (B) is sorbitol.
4. The release film according to any one of claims 1 to 3, wherein the compound (C) is a polyester resin.
5. The release film according to any one of claims 1 to 4, wherein the base film is a polyester film.
6. A film laminate comprising the release film according to any one of claims 1 to 5 bonded to an optical member via a silicone adhesive layer.
7. The film laminate according to claim 6 , wherein the optical member is a resin film or a glass substrate.
8. The film laminate according to claim 7 , wherein the resin film is selected from the group consisting of a polyester film, a polyimide film, and a cyclic polyolefin film.
9. 9. The film laminate according to claim 7, which is a laminate film having a functional layer provided on a surface of the resin film that contacts the silicone adhesive layer.
10. The film laminate according to claim 9 , wherein the functional layer is another release layer.
11. The film laminate of claim 10 , wherein the other release layer comprises a curable silicone resin.
12. The film laminate according to any one of claims 6 to 11, having a total thickness of 200 µm or less.
13. The release film according to any one of claims 1 to 5, which is for protecting a silicone adhesive layer.
14. The film laminate according to any one of claims 6 to 12, which is for protecting a silicone adhesive layer.
15. The release film according to claim 13 , which is for in-vehicle use.
16. The film laminate according to claim 14, which is for use in a vehicle.
Citation Information
Patent Citations
Antistatic material and antistatic film
JP2008179809A
Mold release film with antistatic property
JP2010006079A
Mold release film
JP2011201035A
Release film having excellent static electricity proofness, and method of manufacturing same
JP2012140008A
Release film
JP2014151573A